The Relationship Between Family Anxiety Levels and Patient Information Needs in the ICU of Ananda Hospital, Bekasi - M. Irhas Said; I Gede Wisma Prayoga; Imas Mulyani (Jurnal Ners, 2026)
Family members of patients admitted to the Intensive Care Unit (ICU) often experience high levels of anxiety due to critical patient conditions, uncertainty, and limited access to clear medical information. Anxiety may increase when families perceive that their information needs regarding diagnosis, treatment, and patient progress are not adequately fulfilled. Understanding the relationship between family anxiety levels and information needs is essential to improve family-centered care in ICU settings. This study aimed to examine the relationship between family anxiety levels and information needs among family members of patients treated in the ICU.This study employed a quantitative descriptive correlational design with a cross-sectional approach. The study was conducted in the Intensive Care Unit of Ananda Hospital Bekasi, Indonesia, from November to December 2025. A total of 25 respondents were selected using total sampling. Data were collected using the Hamilton Anxiety Rating Scale (HARS) to measure family anxiety levels and an adapted Critical Care Family Needs Inventory (information domain) to assess information needs. Data analysis included univariate analysis and bivariate analysis using the Chi-square test with a significance level of 0.05. The results showed that most respondents had high information needs (60%) and experienced high levels of anxiety, including severe anxiety (36%) and panic anxiety (32%). Statistical analysis revealed a significant relationship between family information needs and anxiety levels (p = 0.001). Families with higher information needs tended to experience higher levels of anxiety while accompanying patients in the ICU. This study demonstrates a significant association between family anxiety levels and information needs in ICU settings. Insufficient fulfillment of information needs may intensify anxiety among family members of critically ill patients. These findings highlight the importance of effective communication and comprehensive information delivery by healthcare professionals to reduce family anxiety and support family-centered care in intensive care units.